Implementasi Senam Hipertensi Untuk Meningkatkan Kualitas Hidup Lansia Di Wilayah Kerja UPT. Puskesmas Kampung Baru - Kiki Handayani; Mona Hastuti (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Hypertension is one of the main health problems in the elderly that can reduce the quality of life and increase the risk of complications such as stroke and kidney failure. Hypertension treatment is not only through pharmacological therapy, but also non-pharmacological interventions such as hypertension exercise which has been proven effective in lowering blood pressure. This study aims to implement and evaluate the effect of hypertension exercise on reducing blood pressure in the elderly in the work area of ​​the Kampung Baru Health Center UPT. The method used is a case study of a 71-year-old elderly with blood pressure of 160/100 mmHg. The exercise intervention was carried out for seven consecutive days with blood pressure measurements taken before and after the intervention. The results showed a decrease in blood pressure and complaints of headaches, as well as an increase in patient knowledge about hypertension. Hypertension exercise has been proven to be an effective independent nursing intervention to lower blood pressure and improve the quality of life of the elderly.